Desmoid tumour of the chest wall in paediatric post-operatory of heart transplant - Freitas Filho, Orival de; Nakahira, Evelyn Sue; Schmidt Junior, Aurelino Fernandes; Azeka, Estela; Jatene, Marcelo Biscegli; Pego-Fernardes, Paulo Manuel (Frontiers in Pediatrics, 2022)
We will report a case of a desmoid tumour (DT), which developed at the surgical site of the pacemaker after a late childhood heart transplant. Patients with idiopathic dilated cardiomyopathy followed up in the paediatric cardiology service. It evolved with the dissociation of ventricular rhythm caused by severe heart failure, which led to the implantation of a cardiac resynchronization device prior to heart transplantation. The progression to end-stage heart disease culminated in a heart transplant at 12 years old. One year after the transplant, at the age of 13 years, he presented a progressively growing mass on the generator site of the resynchronization device. The initial decision was to remove the device. During the removal surgery, there was no haematoma or fluid collection. However, there was a progression of the lesion. The lesion was biopsied with the anatomopathological diagnosis of a DT. Resection surgery happened 4 months after the start of the mass growth. At that time, the tumour reached 20 cm in diameter. The lesion infiltrated the pectoralis major muscle and this muscle was resected partially en bloc with the lesion. The defect had primary closure. The patient evolved without postoperative complications and was discharged on the 14th postoperative day. The surgical specimen came with negative circumferential margins. However, the deep margin was microscopically positive. Due to deep involvement, the patient underwent adjuvant radiotherapy. Currently, the patient is under clinical follow-up and has no evidence of tumour recurrence. DT is a rare tumour, with unpredictable courses. Surgery can be considered in the progression of lesions. Treatment is justified by long survival after a heart transplant and in DT patients. DT is a differential diagnosis to be considered in progressive growth lesions.